The ethics of economic responsibility - Lüfter, Ralf (Routledge, 2021)
"The Ethics of Economic Responsibility raises fundamental ethical questions related to the conceptualization of economic responsibility, that is: the imperative to fulfil certain economic obligations. It builds on a basic characterization of the question of ethics in order to introduce responsibility as a constitutive element for a new determination of economic knowledge. Drawing on the metaphysical tradition of philosophy, the book explores the distinction between "operability-based-responsibility" and "end-in-itself-based responsibility" and also considers what is tentatively called "being-related responsibility". By presenting these arguments about the notion of economic responsibility, the book contributes to the growing calls for ethical questions to not be merely complementary to the ongoing discourse of economic sciences, but rather to sit at its core, in such a way as to restore the intrinsic ethical dimension of economics itself. The book marks a significant contribution to the literature on the philosophy of economics, applied ethics more broadly, and the critical discourse concerning mainstream economics."
Includes bibliographical references and index
Keywords: Unternehmensethik; Corporate Social Responsibility; Integrative Wirtschaftsethik; Geschäftsgebaren; Wirtschaftsethik / (DE-627)091400902 / (DE-STW)18130-4; Verantwortung / (DE-627)091396999 / (DE-STW)19733-4; Economics / Moral and ethical aspects; Ethics; Responsibility